The Frequency of Diabetic Macular Edema and its Systemic Risk Factors: A Cross-Sectional Study - Darikta Dargahi Shaikh, Fayaz Ali Kalhoro, Sajida Parveen Shaikh, Rizwana Dargahi Shaikh, Rajesh Rathi, Tanweer Ahmed Shaikh (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The goal of this research was to use optical coherence tomography to assess the prevalence of diabetic macular edoema and to determine the impact of systemic results and risk factors on the progression of DME. Material and Methods: This cross-sectional research was carried out at the Department of Ophthalmology, Chandka Medical College & Shaheed Mohtarma Benazir Bhutto Medical University Larkana. Patients were asked to fill out questionnaires about their health and lifestyle habits like smoking and alcohol consumption as well as their hemoglobin A1C and lipid profiles, as well as the duration of their diabetes, and the type of diabetes they had. There was an investigation into the link between systemic findings and DME Results: A total of 150 cases met the study’s eligibility requirements. Males comprised 84 (56%) of the 150 participants, while females comprised 66 (44%). Sixty-five patients (43.33%) tested positive for DME, while 85 patients (56.66%) tested positive for DR. DME participants had HbA1c levels of 9.39 ± 1.67percent, whereas participants without DME had levels of 7.02 ± 3.23 percent and p=0.326; but no connection was found between the two measurements. There was a statistically significant difference between the mean serum creatine concentrations in cases with and without DME (p=0.011). For DME, a statistically significant difference (P-value = 0.001) was found between normal-albuminuric, microalbuminuric, and macroalbuminuric patients. Using the DME frequency in phakic and pseudophakic eyes as a guide, figure 2 below illustrates the results. Conclusions: Diabetic macular edema was seen in 43.33% of cases in the current study. An OCT-based study revealed that DME is common in Larkana Sindh. Regulating DME risk factors can help prevent or limit the development of DME, and treatment response may be improved.